Endobronchial valve therapy in patients with homogeneous emphysema: results from the IMPACT study - Valipour, Arschang; Herth, Felix; Eberhardt, Ralf (American journal of respiratory and critical care medicine, 2016)
Rationale: Endobronchial valves (EBVs) have been successfully used in patients with severe heterogeneous emphysema to improve lung physiology. Limited available data suggest that EBVs are also effective in homogeneous emphysema.Objectives: To evaluate the efficacy and safety of EBVs in patients with homogeneous emphysema with absence of collateral ventilation assessed with the Chartis system.Methods: Prospective, multicenter, 1:1 randomized controlled trial of EBV plus standard of care (SoC) or SoC alone. Primary outcome was the percentage change in FEV1 (liters) at 3 months relative to baseline in the EBV group versus the SoC group. Secondary outcomes included changes in FEV1, St. George’s Respiratory Questionnaire (SGRQ), 6-minute-walk distance (6MWD), and target lobe volume reduction.Measurements and Main Results: Ninety-three subjects (age, 63.7 ± 6.1 yr [mean ± SD]; FEV1, % predicted, 29.3 ± 6.5; residual volume, % predicted, 275.4 ± 59.4) were allocated to either the EBV group (n = 43) or the SoC group (n = 50). In the intention-to-treat population, at 3 months postprocedure, improvement in FEV1 from baseline was 13.7 ± 28.2% in the EBV group and −3.2 ± 13.0% in the SoC group (mean between-group difference, 17.0%; P = 0.0002). Other variables demonstrated statistically and clinically significant changes from baseline to 3 months (EBV vs. SoC, respectively: SGRQ, −8.63 ± 11.25 vs. 1.01 ± 9.36; and 6MWD, 22.63 ± 66.63 m vs. −17.34 ± 52.8 m). Target lobe volume reduction at 3 months was −1,195 ± 683 ml (P < 0.0001). Of the EBV subjects, 97.2% achieved volume reduction in the target lobe (P < 0.0001). Procedure-related pneumothoraces occurred in 11 subjects (25.6%). Five subjects required removal/replacement of one or more valves. One subject experienced two valve migration events requiring removal/replacement of valves.Conclusions: EBV in patients with homogeneous emphysema without collateral ventilation results in clinically meaningful benefits of improved lung function, exercise tolerance, and quality of life.